(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In the paper the distinctive features of the notions “criteria of the development of foreign students’ polycultural competence”, “factors”, “levels of development of foreign students’ polycultural competence” are defined; viewpoints of Ukrainian and foreign scientists on the polycultural competence structure and peculiarities of criteria choice are analyzed; criteria of development of foreign students’ polycultural competence in studying Ukrainian are cognitive, motive-value, behavioral-practical, axiological). Cognitive criterion indicates knowledge of the language, culture, traditions, peculiarities of communication, common rules of norms of behavior during interaction with other cultures’ representatives. Motive-value criterion contains the complex of motives and needs which motivates a student for polycultural competence development, evaluation attitude of a student to some deeds and actions which is aimed to meet needs during intercultural communication. Behavioral-practical criterion implies attainment of intercultural interaction experience; practical skills of obtained knowledge, mastering of particular communicative skills and ability of solving definite tasks of intercultural interaction; ability to start intercultural communication with representatives of other cultures, to reflect own activity and behavior. Axiological criterion contains the complex of moral, aesthetic values, tolerance, humanism, national and ethnic self-consciousness. In the paper the conformity of criteria, factors and levels of polycultural competence development of accurate evaluation of foreign students during the Ukrainian language training are analyzed.